1993
DOI: 10.1164/ajrccm/148.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Dust Exposure and Chronic Obstructive Pulmonary Disease: A Systematic Overview of the Evidence

Abstract: The object of this study was to assess the relationship between occupational dust exposure and chronic obstructive pulmonary disease (COPD). Studies were identified using MEDLINE (January 1966 to July 1991), SCISEARCH, manual review of reference lists, and personal contact with more than 30 international experts. Studies of COPD, lung function, emphysema, chronic bronchitis, or mortality in workers exposed to nonorganic dust were retrieved. Studies were included if dust exposure was measured quantitatively, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
151
0
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(168 citation statements)
references
References 24 publications
11
151
0
6
Order By: Relevance
“…The induction time from exposure to the detection of early COPD is often long (decades). Identification and measurements of relevant exposures over a prolonged period of time are generally not performed and thus are unavailable for research with few exceptions (8).…”
mentioning
confidence: 99%
“…The induction time from exposure to the detection of early COPD is often long (decades). Identification and measurements of relevant exposures over a prolonged period of time are generally not performed and thus are unavailable for research with few exceptions (8).…”
mentioning
confidence: 99%
“…(25)(26) As alterações clínicas e funcionais observadas, embora guardem certa relação com as alterações radiográficas, podem ser encontradas em indiví-duos expostos sem evidências radiográficas de silicose.…”
Section: Limitação Crônica Ao Fluxo Aéreo E Câncer Pulmonarunclassified
“…Although cigarette smoking is the most important risk factor worldwide for COPD, occupational exposures to mineral and organic dusts, irritant gases and fumes, and to other industrially produced or used agents have been established as risk factors for COPD [2][3][4][5][6][7][8][9][10][11][12][13][14]. Industryand population-based epidemiological studies have reported increased risk of COPD due to occupational exposures or due to employment in certain industries or job categories.…”
Section: Introductionmentioning
confidence: 99%
“…Industryand population-based epidemiological studies have reported increased risk of COPD due to occupational exposures or due to employment in certain industries or job categories. Occupational groups reported to have increased risk of COPD include coal miners, hard rock miners, tunnel workers, concretemanufacturing workers, construction workers, agricultural workers, and some manufacturing workers [2,3,[6][7][8][9]. COPD etiology is multi-factorial in nature and is strongly associated with non-occupational factors such as tobacco smoking.…”
Section: Introductionmentioning
confidence: 99%